PERANCANGAN PARAMETER PI-DIGITAL DENGAN METODE SYMMETRICAL OPTIMUM PADA DIRECT TORQUE CONTROL MOTOR TRAKSI TIGA FASA - Dharma Abiyyu Allam; Moch. Rusli; Bambang Siswojo (Jurnal Mahasiswa TEUB, 2023)
This study discusses the design of a proportional-integral (PI) controller with a three-phase traction motor as the plant to be controlled. The modulation technique to control the switching on the rectifier uses space vector pulse-width modulation (SVPWM) where the three-phase current and voltage are represented in rotating synchronous coordinates. The control strategy, namely vector control, is used to support the SVPWM modulation technique to provide optimal DC voltage output. Optimal controller design is obtained by tuning the gain parameters of the cascade of speed, flux, and torque controllers using the optimum symmetrical method. The test was carried out by simulating the MATLAB/Simulink software to show the speed stability of a three-phase traction motor. Three-phase traction motor produces an output speed of 158 rad/s, reaches a steady state condition of 0.275 seconds, there is no overshoot, Steady State error is 0.64%. Keywords: Three phase traction motor, Direct Torque Control, PI controller, symmetrical optimum. DAFTAR PUSTAKA[1] Alvi, Vania Kurnia., 2020., "Pengaturan Kecepatan Motor Induksi 3- phase dengan Metode Direct Torque Control," JURNAL INOVTEK SERI ELEKTRO, vol. II, no. 3, pp. 159-167, Desember 2020.[2] Garg, R., dll., 2014., "A Comparative Study between Field Oriented Control and Direct Torque Control of AC Traction Motor," in IEEE International Conference on Recent Advances and Innovations in Engineering, Jaipur, 2014.[3] Goolak, S., Liubarskyi, B., Sapronova, S., Tkachenko, V., Riabov, I., Glebova, M. (2021). Improving a model of the induction traction motor operation involving nonsymmetric stator windings. EasternEuropean Journal of Enterprise Technologies, 4 (8 (112)), 45– 58. doi: https://doi.org/10.15587/1729-4061.2021.236825[4] Nugroho, Septian Eko., 2021., "SISTEM PENGENDALIAN KECEPATAN MOTOR 3- PHASE MENGGUNAKAN METODE DIRECT TORQUE CONTROL (DTC)," Jurnal Teknik Elektro, vol. X, no. 1, pp. 81- 90, 2021.[5] Suda, K. R. S., dll., 2021., "PENGATURAN KECEPATAN MOTOR INDUKSI 3 FASA DENGAN MENGGUNAKAN PEMODELAN SISTEM (DTC) DIRECT TORQUE CONTROL," Jurnal Pendidikan Teknologi dan Kejuruan, vol. XVIII, no. 2, pp. 237- 248, Juli 2021.[6] I. D. Landau and A. Voda, “The ‘Symmetrische Optimum’ and the AutoCalibration of PID Controllers,” IFAC Proceedings Volumes, vol. 25, no. 14, pp. 407–412, Jul. 1992, doi: 10.1016/s1474-6670(17)50768-5.[7] Mukti, Harrij., 2014 “IMPLEMENTASI DIRECT TORQUE CONTROL DALAM PENGATURAN KECEPATAN MOTOR INDUKSI”., Jurnal ELTEK, Vol 12 No 01, April 2014 ISSN 1693-4024[8] LAZRAK, LOUBNA., etc., 2005., “DIRECT CONTROL OF THE STATOR FLUX AND TORQUE OF THE THREEPHASE ASYNCHRONOUS MOTOR USING A 2-LEVEL INVERTER WITH SINUSOIDAL PULSE WIDTH MODULATION”., Journal of Theoretical and Applied Information Technology., 30th September 2018. Vol.96. No 18[9] Zelechowski, M., Kazmierkowski, M. P., & Blaabjerg, F. (2005, June). Controller design for direct torque controlled space vectormodulated (DTC-SVM) induction motor drives. In Proceedings of the IEEE International Symposium on Industrial Electronics, 2005. ISIE 2005. (Vol. 3, pp. 951-956). IEEE.[10] Putri, Frieda Irnanda., 2014., “REKAM JEJAK KERUSAKAN TRAKSI MOTOR LOKOMOTIF UNTUK MENENTUKAN INTERVAL WAKTUPENGGANTIAN KOMPONEN BERDASARKAN KEANDALAN (RELIABILITAS)”., Jurusan Teknik Mesin, Fakultas Teknik, UniversitasNegeri Surabaya., Volume 02 Nomor 02 Tahun 2014, 53-60[11] P. Woolf, “CHEMICAL PROCESS DYNAMICS AND CONTROLS.” [Online].Available: https://LibreTexts.org